Reaktualisasi Maqasid Al-Shariah dalam Etika Ekonomi Islam di Era Digitalisasi Global - Sulistiyah Sulistiyah; Arifah Rohmatul Hidayah (AKADEMIK: Jurnal Mahasiswa Ekonomi & Bisnis, 2026)
The rapid expansion of global digitalization has significantly transformed economic activities, enhancing efficiency while simultaneously generating ethical challenges such as data exploitation, consumer manipulation, and profit-oriented business practices that often neglect moral considerations. This study aims to examine the relevance of maqāṣid al-Shariah as an ethical and normative framework for guiding Islamic economic practices in the digital era toward justice, sustainability, and social welfare. Employing a qualitative library research method, this study analyzes contemporary and classical literature sourced from national and international academic publications related to Islamic economics, digital transformation, and maqāṣid-based ethics. The findings reveal that the core principles of maqāṣid al-Shariah including the protection of religion, life, intellect, wealth, and progeny provide a comprehensive ethical foundation for regulating digital economic activities across production, consumption, and public policy domains. These principles emphasize a balance between technological innovation and moral responsibility, ensuring transparency, fairness, data protection, and long-term societal well-being. This study contributes to the discourse on Islamic digital economics by positioning maqāṣid al-Shariah not merely as a normative concept but as a strategic ethical framework capable of addressing contemporary digital economic challenges in a holistic and sustainable manner.